A study of factors influencing housing developers to choose appropriate prcurement strategy - Raja Nurfarhana, Raja Razalli (2014)
The purpose of this research is to identify and rank the factors influencing housing developers the most to choose appropriate procurement strategy. The selection of an appropriate procurement strategy is becoming an increasingly important issue due to a complex decision-making that has to be made by clients during early project lifecycle. A comprehensive literature review of various procurement strategies and factors which influence the selection of an appropriate strategy for housing development projects in Johor was conducted. A survey questionnaire was carried out to obtain housing developers’ views on factors that influence the selection of procurement strategy for their entire projects. A total of 30 housing development companies were responded to the survey. The data was then analysed using the Statistical Package for Social Sciences (SPSS) and the factors ranked according to their means. The results shows that the top three important factors that most influenced are client budget requirement, client financial capability and client experience. This research also has ranked the factors according to their degree of influenced that is client budget requirement is at the first position, followed by client financial capability at the second position and client experience at the third position. One recommendation for future research is to focus on developing models for the selection of an appropriate procurement strategy instead of identifying influence factors